Evidence of progenitor cells in the adult human cochlea: sphere formation and identification of ABCG2 - Massucci-Bissoli, Milene; Lezirovitz, Karina; Oiticica, Jeanne; Bento, Ricardo Ferreira (Clinics, 2017)
OBJECTIVES: The aim of this study was to search for evidence of stem or progenitor cells in the adult human cochlea by testing for sphere formation capacity and the presence of the stem cell marker ABCG2. METHODS: Cochleas removed from patients undergoing vestibular schwannoma resection (n=2) and from brain-dead organ donors (n=4) were dissociated for either flow cytometry analysis for the stem cell marker ABCG2 or a sphere formation assay that is widely used to test the sphere-forming capacity of cells from mouse inner ear tissue. RESULTS: Spheres were identified after 2-5 days in vitro, and the stem cell marker ABCG2 was detected using flow cytometric analysis after cochlear dissociation. CONCLUSIONS: Evidence suggests that there may be progenitor cells in the adult human cochlea, although further studies are required.